RESULTS OF A STUDY OF THE INFLUENCE OF QUALITATIVE INDICATORS OF THE USE OF ROLLING STOCK ON THE COST OF FREIGHT TRANSPORTATION - ZORINA, Olena; KAMENEVA, Nataliya; KIРRENKO Alina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article presents the results of a study of the impact on the cost of freight transportation of qualitative indicators of the use of rolling stock. The cost of transportation is a complex economic indicator. This indicator evaluates the costs of all types of resources for transportation. Reducing the cost of transportation indicates a reduction in resource costs. The cost of freight transportation is influenced by the type of traction, labor productivity, material consumption and energy intensity of transportation. The change in the qualitative indicators of the use of rolling stock has a significant impact on the economic indicators of the operational activities of railway transport. The cost of freight transportation can be reduced with the efficient use of rolling stock. This is possible by increasing the dynamic load of the loaded car, the mass of the train, the productivity of the freight car and the locomotive, sectional speed, and the average daily mileage of the freight car and the locomotive. Two areas of research are distinguished on the basis of determining the cost of transportation. The first direction is to identify the relationship between costs and traffic volumes. The second direction is to identify the dependence of costs on individual meters. The impact of qualitative indicators of the use of rolling stock on the cost of freight transportation is determined by the method of unit cost rates. This method establishes the dependence of the cost of freight transportation on the qualitative indicator of the use of rolling stock. As a result of the study, qualitative indicators of the use of rolling stock have been identified, which have a significant impact on the cost of freight transportation. The results of the study can be used for further development of technical and operational measures to improve the efficiency of the railway transport of Ukraine.